2018
DOI: 10.1016/j.vaccine.2018.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Measuring vaccine hesitancy: Field testing the WHO SAGE Working Group on Vaccine Hesitancy survey tool in Guatemala

Abstract: Our results suggest problems with interpretation of the VHS, especially in the presence of vaccine shortages and using a Likert scale that does not resonate across diverse cultural settings. Our factor analysis suggests that the Likert scale items are more one-dimensional and do not represent the multiple constructs of vaccine hesitancy. We suggest more work is needed to refine this survey for improved reliability and validity. Clinical Trial Registry: NCT02567006.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
142
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 40 publications
11
142
0
6
Order By: Relevance
“…The belief of 22 (40.0%) of 55 participants who were previously hesitant has changed; they stated that now they believe vaccines are necessary. Vaccine hesitancy is a dynamic situation, and it may change over time and circumstances (12)(13)(14). Our outcome is notable because it shows that when an infectious agent and a pandemic arises, people need vaccination, and their opinions about vaccines may change.…”
Section: Discussionmentioning
confidence: 89%
“…The belief of 22 (40.0%) of 55 participants who were previously hesitant has changed; they stated that now they believe vaccines are necessary. Vaccine hesitancy is a dynamic situation, and it may change over time and circumstances (12)(13)(14). Our outcome is notable because it shows that when an infectious agent and a pandemic arises, people need vaccination, and their opinions about vaccines may change.…”
Section: Discussionmentioning
confidence: 89%
“…The PACV survey gives instructions on how to convert to and interpret an overall vaccine hesitancy score, whereas we came up with ad hoc measures in the WHO SAGE Vaccine Hesitancy Scale. We note several limitations of using this scale, including items L5, L9, and L10 not correlating well with the other items (perhaps as a result of their questions having reversed directionality relative to the other questions) [14,16]. Although this survey was simple to administer and translate, future research should identify how individuals in different regions of the world with different educational backgrounds interpret a 5-point Likert scale.…”
Section: The Who Sage Vaccine Hesitancy Scalementioning
confidence: 99%
“…The WHO SAGE also developed a 10-item vaccine hesitancy scale to assess vaccine hesitancy and vaccine perceptions. [12] This has been implemented in Canada [13] and several LMICs-including Guatemala [14], Ethiopia [15], and China [16]. These studies have revealed interesting trends in the data-notably that a large proportion of the population believes in the effectiveness of vaccines, in general, while harboring some concerns about safety and the utility of certain vaccines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In a study involving 720 parents in Guatemala, while none of the parents refused vaccination, only 1.1% expressed reluctance or hesitancy to have their children vaccinated. 17 A population-based study from Croatia found the rates of vaccine refusal and hesitancy as 10.6 and 19%, respectively, with higher rates at younger ages. 18 A study conducted in Malaysia reported the rate of parental vaccine hesitancy to be 11.6%, being more prevalent among unemployed parents, younger parents, parents with fewer children, and non-Muslim persons.…”
Section: Discussionmentioning
confidence: 99%